Towards ontology as knowledge representation for intellectual capitals measurement - Zadjabbari, B.; Wongthongtham, Pornpit; Dillon, Tharam S. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
For many years, physical asset indicators were the main evidence of an organisation's successful performance. However, the situation has changed after information technology revolution in the knowledge-based economy. Since 1980?s business performance has not been limited only to physical assets instead intellectual capitals are increasingly playing a major role in business performance. In this paper, we utilize ontology as a tool for knowledge representation in the domain of intellectual capital measurement. The ontology classifies ways of intangible capital measurement.